Preventive treatment patterns and treatment satisfaction in migraine: results of the OVERCOME (EU) study - Julio Pascual; Tommaso Panni; Grazia Dell’Agnello; Saygin Gonderten; Diego Novick; Stefan Evers (The Journal of Headache and Pain, 2023)
Abstract Background Insights into the burden, needs and treatment of migraine from internet-based surveys in diverse real-world migraine populations are needed, especially at a time when novel preventive migraine medications are becoming part of the therapeutic armamentarium. The objectives of this analysis are to describe traditional preventive (orals and onabotulinum toxin A) treatment patterns in the OVERCOME (EU) study migraine cohort, as well as treatment patterns and patient satisfaction with current treatment in a subgroup of respondents eligible for migraine preventive medication. Methods The cross-sectional non-interventional OVERCOME (EU) study was conducted (October 2020–February 2021) via an online survey among adults (aged ≥ 18 years) resident in Germany or Spain. Participants, registered in existing online panels, who were willing to provide consent were considered. The migraine cohort included participants reporting headache/migraine in the past year, identified based on a validated migraine diagnostic questionnaire and/or self-reported physician diagnosis. A subgroup of survey respondents defined as eligible for migraine preventive medication at the point in time the cross-sectional survey was taken was also analysed. Variables assessed included sociodemographic and migraine-related clinical characteristics, preventive (traditional and calcitonin gene-related peptide monoclonal antibodies) treatment patterns and patient satisfaction with current treatment. Results are descriptive only. Results Of the 20,756 participants in the migraine cohort, 78.5% sought professional medical care, 50.8% received a migraine diagnosis and only 17.7% had ever used preventive medication. Half (53.3%) of participants currently using preventives took their most recent medication for six months or less. Most patients (73.9%) classified as eligible for preventive medication (based on headache frequency and/or at least moderate disability due to migraine) reported not using traditional preventives and many of those who did (66.8%) were not satisfied with their current standard of care. Conclusions Our findings highlight the low proportion of people diagnosed with migraine despite a higher rate of consultation and suggest the need for better access to treatment for people with migraine and new preventive therapies with improved efficacy and safety profiles to improve adherence and patient satisfaction.